EDITING FOR THE SHORT FILM "BAYANGKU, BAYANGMU" - Kaban, Leandro Tristan; Al Ansory, Muchammad Zaenal; Barlian, Yelly Andriani (eProceedings of Art & Design, 2024)
Due to the COVID 19 pandemic, all activities around the world had been halted and people are required to stay inside their houses until further notice. Indonesia, as one of the affected countries, has had setbacks on many sectors especially in the education field. This research is done to analyse and dive into the effect of social isolation due to COVID 19 towards the mental health of students using a cinematic narrative. With the creation and portrayal of the short film "Bayangku, Bayangmu," it aims to depict how isolated individuals felt during the pandemic era in a cinematic view. The sense of detachment from society and having severe social withdrawal is a phenomenon that many people can relate and interpret differently, hence why many interpretations in the form of moving visual media had been made. This moving visual media artwork is used not only as a platform that gives people perspectives of the phenomenon, but also as a representation of the unheard feelings of a tormented-individuals. With the author involvement in the production of this movie as the editor, author will integrate editing technique, colour grading and sound design into the film to enhance and create a cinematically appealing psychological-drama film about social isolation for audience to watch. Methodologically, qualitative analysis such as observation, questionnaire, interview, literature and visual review are used to gain more insights and knowledge as reference for editing. In conclusion, the main goal of the short film "Bayangku, Bayangmu" is that it can be seen not only through a cinematic view, but also through the mental health aspect which had been represented. Keywords: mental health, social isolation, pandemic, film, editing